A new milestone in corporate regulation: procedural legalisation, standards of transnational corporate behaviour and lessons from financial regulation and anti-bribery regulation. Issue 2 (3rd July 2017) - Chiu, Iris H-Y.; Donovan, Anna
ABSTRACT: Governing transnational corporate behaviour is a challenging area that has been canvassed in much academic literature. Transnational corporations make extensive use of regulatory arbitrage and corporate structures in order to avoid or mitigate the reach of legal and regulatory governance. Moreover, international soft law standards that encourage multinational corporations to be more responsible are not always effective or enforceable. Against this context, we explore an emerging regulatory trend in corporate regulation that has the potential to overcome some of the currently perceived limitations in the regulatory governance of transnational corporations. There is an intensifying trend in adopting procedural regulatory strategies for corporations. This involves prescribing various control systems and processes that corporations have to institute, such as compelling them to develop due diligence requirements within their commercial operations. We suggest this is a new milestone in 'new governance' design that we call 'procedural legalisation'. Procedural legalisation is being adopted at an unprecedented level in financial sector and corporate regulation, and offers a new promise in changing corporate culture and behaviour, possibly addressing longstanding limitations in effectively regulating corporations. We present two case studies to explore how procedural legalisation is applied to regulate corporations in the financial sector and in anti-bribery.